The Convergence of Artificial Intelligence and Bio-Informatics: Shaping the Future of Social Science Research - Dr. Suresha K C, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The growth of technology especially in the field of Artificial Intelligence and BioInformatics is changing the landscape of many subjects, especially social science. SocialScience being primarily concerned with the study of human relations in society